Mixed culture purple phototrophic bacteria is an effective fishmeal replacement in aquaculture - Jérôme Delamare-Deboutteville; Damien J. Batstone; Minami Kawasaki; Samuel Stegman; Michael Salini; Simon Tabrett; Richard Smullen; Andrew C. Barnes; Tim Hülsen (Water Research X, 2019)
Aquaculture is the fastest growing animal food production industry, now producing 50% of all food fish. However, aquaculture feeds remain dependent on fishmeal derived from capture fisheries, which must be reduced for continued sustainable growth. Purple phototrophic bacteria (PPB) efficiently yield biomass from wastewater with high product homogeneity, a relatively high protein fraction, and potential added value as an ingredient for fish feeds. Here we test bulk replacement of fishmeal with PPB microbial biomass in diets for Asian sea bass (Lates calcarifer), a high value carnivorous fish with high protein to energy requirement. Mixed culture PPB were grown in a novel 1 m3 attached photo-biofilm process using synthetic and real wastewater. Four experimental diets were formulated to commercial specifications but with the fishmeal substituted (0%, 33%, 66%, and 100%) with the synthetic grown PPB biomass and fed to a cohort of 540 juvenile fish divided amongst 12 tanks over 47 days. Weight and standard length were taken from individual fish at 18, 28, and 47d. No significant difference in survival was observed due to diet or other factors (94–100%). There was a negative correlation between PPB inclusion level and final weight (p = 5.94 × 10−5) with diet accounting for 4.1% of the variance over the trial (general linear model, R2 = 0.96, p = 1 × 10−6). Feed conversion ratio was also significantly influenced by diet (p = 6 × 10−7) with this factor accounting for 89% of variance. Specifically, feed conversion ratio (FCR) rose to 1.5 for the 100% replacement diet during the last sample period, approximately 1.0 for the partial replacement, and 0.8 for the nil replacement diet. However, this study demonstrates that bulk replacement of fishmeal by PPB is feasible, and commercially viable at 33% and 66% replacement. Keywords: Fishmeal, Photobioreactor, Purple phototrophic bacteria, Single cell protein